A comprehensive review on the grinding process: Advancements, applications and challenges. (November 2022) - Kishore, Kamal; Sinha, Manoj K; Singh, Amarjit; Archana,; Gupta, Munish K; Korkmaz, Mehmet Erdi
Grinding is a manufacturing process which significantly contributes in producing high precision and durable components required in numerous applications such as aerospace, defence and automobiles. This review article is focused to uncover history, witness the present and predict the future of the grinding process. While going through the literature, it has been observed that minimal work has been done in explaining the history, present status and future scopes of the grinding process. In this era of information and environmental awareness, sustainability aspects have become a primary concern of almost every research field. In the grinding process too, the research work includes ecological elements such as reducing the consumption of cutting fluids through minimum quantity lubrication, utilizing cryogenics, hybrid lubrication and cooling techniques that are still required to be explored critically. Further, some significant findings of the prevailing research in grinding include modification in grinding wheel surface, merging different grinding principles such as usages of the textured grinding wheel, ultrasonic grinding, 3D printing of grinding wheel and artificial intelligence in grinding are also presented. Another unascertained problem is the management of grinding swarf, which is being attended to by recycling it to fabricate composites which is expected to be another prominent domain of research. Further, the advancements taking place exhibit the potential of the grinding process, suggesting that its future is bright and ever-growing.